Pengembangan Motorik Halus Melalui Metode Melipat Kertas Origami Pada Anak Didik Kelompok B Semester I TK Dharma Wanita 1 Botoreco Kundurab Blora Tahun 2015/2016 - SRIYATUN, SRIYATUN; , Drs. M. Yahya, M.Si (2015)
Sriyatun/A531130034. Developing Soft Psychomotor Skill Through Paper Folding on Students of Dharma Women 1 Kindergarten Botoreco, Blora. Publication of Scientific Article. Department of Early Childhood Education, School of Teacher Training and Education, Muhammadiyah University of Surakarta. October, 2015. The purpose of this research is aims to develop fine motor skillof children through paper folding method. This research is a classroom action research (CAR) with two working procedure cycle consists of four phases: Planning, action, observation and reflection. Method of data collection observation and field notes. The research showed that the average child's motor before action was 33.5%, after the learning by activity in the first cycle of fine motor was 69.16% and in the second cycle folding was 84.60%. Overall, folded activity could improve fine motor skill in group B of Dharma Women 1 Kindergarten Botoreco, Blora.